1992
DOI: 10.1128/aac.36.12.2686
|View full text |Cite
|
Sign up to set email alerts
|

The anti-hepatitis B virus activities, cytotoxicities, and anabolic profiles of the (-) and (+) enantiomers of cis-5-fluoro-1-[2-(hydroxymethyl)-1,3-oxathiolan-5-yl]cytosine

Abstract: The anti-hepatitis B (anti-HBV) activities of the (-) and (+) enantiomers of cis-5-fluoro-1-[2-(hydroxymethyl)-1,3-oxathiolan-5-yl]cytosine (2'-deoxy-3'-thia-5-fluorocytosine [FTC]) were studied by using an HBVtransfected cell line (HepG2 derivative 2.2.15, subclone P5A). The (-) isomer was found to be a potent inhibitor of viral replication, with an apparent 50% inhibitory concentration of 10 nM, whfle the (+) isomer was found to be considerably less active. Both isomers showed miimal toxicity to HepG2 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(140 citation statements)
references
References 26 publications
7
133
0
Order By: Relevance
“…These studies emphasize the importance of such biochemical studies in the development of novel entities for the treatment of viral infections and underlines the potential role of metabolites such as FMAU in a possible synergistic toxicity with the parent drug. The absence of such mitochondria effects with 3TC (Table II) and (-)-2',3'-dideoxy-5-fluoro-3'-thiacytidine (39), two nucleoside analogs being developed for the treatment of HIV and HBV infections (40)(41)(42) demonstrate that each nucleoside should be considered as a unique entity and further emphasizes the usefulness of that class of compound to treat such viral infections.…”
Section: Resultsmentioning
confidence: 99%
“…These studies emphasize the importance of such biochemical studies in the development of novel entities for the treatment of viral infections and underlines the potential role of metabolites such as FMAU in a possible synergistic toxicity with the parent drug. The absence of such mitochondria effects with 3TC (Table II) and (-)-2',3'-dideoxy-5-fluoro-3'-thiacytidine (39), two nucleoside analogs being developed for the treatment of HIV and HBV infections (40)(41)(42) demonstrate that each nucleoside should be considered as a unique entity and further emphasizes the usefulness of that class of compound to treat such viral infections.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely in view of the fact that both D-and L-FTCMP are substrates of calf thymus dCMPK with a preference for the L-enantiomer (E L/D =8.1) (Furman et al, 1992). No study of the interaction of dCMPK with β-ddCMP or β-FddCMP has been reported.…”
Section: Nucleotide Kinasesmentioning
confidence: 84%
“…Thus, the β-L-enantiomer of dC, or the α-L-and β-L-enantiomers of riboC, araC, xyloC and lyxoC were resistant to human CDA (Shafiee et al, 1998). Similarly, the β-L-enantiomers of 3TC (Chang et al, 1992a), FTC (Furman et al, 1992), FddC (Martin et al, 1997) and Fd4C were not substrates or weak substrates of CDA, contrary to the corresponding β-D-enantiomers. E. coli CDA has been used to develop a process for the production of β-L-3TC in multikilogram amounts, which is based on the exclusive deamination of the D-enantiomer from the racemic mixture (Mahmoudian et al, 1993) (Figure 10).…”
Section: Enantioselectivities Of Nucleoside Deaminases and Phosphorylmentioning
confidence: 99%
“…Furthermore, the 5Ј-triphosphates of L-dC, L-dT, and L-dA each inhibited WHV DNA polymerase with a 50% inhibitory concentration of 0.24 to 1.82 M. In addition, exposure of HepG2 cells to L-dC led to a second 5Ј-triphosphate derivative, i.e., ␤-L-2Ј-dUTP (LdUTP) which also inhibited WHV DNA polymerase, with a 50% inhibitory concentration of 5. (4,19,31,51), L-dC was not a substrate for cytosolic cytidine deaminase, which suggested that the 5Ј-monophosphate metabolite of L-dC may be susceptible to deamination through deoxycytidylate deaminase. The inhibition of HBV replication by these ␤-L-2Ј-deoxynucleosides and inhibition of hepadnaviral polymerase by their corresponding 5Ј-triphosphates suggested that, like most nucleoside analogs, L-dC, L-dT, and L-dA may act by inhibiting the reverse transcription of HBV pregenomic RNA.…”
Section: Vol 45 2001 Antiviral L-nucleosides Specific For Hbvmentioning
confidence: 99%